Fault-tolerant adaptive attitude tracking control of satellite with uncertainty and actuator misalignment in presence of environmental disturbances - Mohammadjavad Hatami; Reza Nadafi; Mansour Kabganian (Scientific Reports)
Abstract In this study, a novel asymptotically stable attitude tracking controller is propounded for a satellite, operating in the existence of environmental disturbances, uncertain inertia matrix, reaction wheel misalignment, and actuator faults. Unlike existing methods, the proposed controller addresses multiple practical challenges simultaneously, including disturbances, uncertainties, misalignment, and faults. Incidentally a key advantage of the proposed controller is its ability to work without requiring a priori knowledge of the upper bound values of uncertainties and disturbances, which is a significant advancement over previous approaches. By deriving the kinematic and kinetic equations of the satellite system and defining appropriate sliding surfaces, the global asymptotic stability of the closed-loop system is guaranteed via Lyapunov theory. Simulation results, incorporating actuator saturation constraints, demonstrate the controller’s performance and robustness, achieving precise attitude tracking with 2% settling time of 7 s and saturation constraint of 0.12 Nm. Furthermore, a MATLAB Multibody simulation model validates the controller, yielding a maximum verification error less than 4% in angular velocity.